Chips as processed food need a Certificate of Home Industry Food - Suprajitno; Mugianti, Sri (STIKes Patria Husada Blitar, 2022)
Chips made from local plants can be used as processed food. Chips produced as a home industry that are consumed are required a Certificate of Home Industry Food (Pangan Industri Rumah Tangga / P-IRT) as a guarantee of food safety. The target of community service is home industry of producing chips that do not yet have a home industry food certificate. And the subject target are six women. The intervention was carried out for the home industry of chips in Kel. Bendo Kec. Kepanjen Kidul Blitar City in April-May 2022. The intervention was assistance for the licensing process. Requirements for issuing certificates of participation in food safety counselling, health of food processors, and information on processed food labels. There were five certificates for processed food certificates for tempe chips, taro chips, potato chips, cassava chips, and sweet tubers chips. The certificate of P-IRT guarantees the safety of processed food for consumption and sale. The impact of the issuance of certificates, sales of chips increased so that family income also increased.